2012
DOI: 10.1620/tjem.227.105
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Laparoscopy in Determining the Optimal Management Plan for Infertile Patients with Suspected Tubal Pathology Revealed by Hysterosalpingography

Abstract: The fallopian tube has numerous functions, including ovum pick-up, the place of fertilization of the ovum and cleavage of the embryo, and transfer of the embryo to the uterus. Tubal pathology impairs functions of the fallopian tube and reduces fertility. The degree of tubal pathology determines the possibility for fertility. The evaluation of the fallopian tube is necessary to determine the management plan of infertility. Hysterosalpingography (HSG) is often performed as a first line approach to assess tubal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…These findings concur with those by Tsuji et al, (12) who found that HSG had a high specificity of diagnosing proximal tubal occlusion or hydrosalpinx and lower sensitivity in cases with peritubal adhesions. The data showed that laparoscopy is a superior technique as far as detection of hydrosalphinx is concerned.…”
Section: Discussion:-supporting
confidence: 92%
See 3 more Smart Citations
“…These findings concur with those by Tsuji et al, (12) who found that HSG had a high specificity of diagnosing proximal tubal occlusion or hydrosalpinx and lower sensitivity in cases with peritubal adhesions. The data showed that laparoscopy is a superior technique as far as detection of hydrosalphinx is concerned.…”
Section: Discussion:-supporting
confidence: 92%
“…This concurs with the findings by Tsuji et al, (12) who conducted a study to find out the impact of patient characteristics such as female age, duration of sub-fertility, and a clinical history without risk factors for tubal pathology. From their study, they estimated that the pooled sensitivity and specificity of HSG were 85% and 87% respectively for any tubal pathology.…”
Section: Discussion:-supporting
confidence: 91%
See 2 more Smart Citations
“…Hysterosalpingography (HSG) is often performed as a first line approach to assess tubal patency and the presence of adhesions; however, HSG has limitations in detecting tubal pathology. 6 Laparoscopy and chromopertubation is widely considered the gold standard test for investigating tubal patency. Additionally, it allows assessment for peritubal disease, adhesions and endometriosis.…”
Section: Introductionmentioning
confidence: 99%